The Procedure for Implementing Diversion in the Juvenile Criminal Justice System in Cases Involving Offenses under Emergency Law: A Critical Study on the Application of Restorative Justice Principles - Agus Efendi; Triono Eddy (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study discusses the application of Diversion for Children in Conflict with the Law (ABH) in criminal cases based on the Emergency Law, especially when the criminal threat exceeds the limit of 7 (seven) years as stipulated in Article 7 paragraph (2) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). The focus of this study is to analyze the interpretation and legal discretion of law enforcement officers, the implementation model of Diversion that remains oriented towards restorative justice, and the obstacles faced in practice. The research method used is normative-empirical with a statutory, conceptual, case, and sociological-juridical approach. Data were obtained through literature studies, interviews, and documentation, then analyzed qualitatively. The results of the study indicate that normatively, cases in the Emergency Law generally do not meet the formal requirements for Diversion because the criminal threat is above 7 years. However, the spirit of child protection and restorative justice can still be pursued through a humanistic, educational, and rehabilitative approach. The main obstacles include legal, structural, and sociological aspects. Therefore, clearer technical guidelines, increased capacity of law enforcement officers, and strengthened roles of families and support institutions are needed to ensure that the handling of children's cases continues to ensure the best interests of the child.